A trial of a school-based cognitive behaviour program for anxiety on 4th Generation Immigrants - Direktör, Cemaliye (Anales de Psicología / Annals of Psychology, 2019)
The purpose of the study in this direction is to examine the effectiveness of the school-based cognitive behaviour program on the reduction in anxiety levels of children at 9-10 years of age. An experimental pattern with pre-test/post-test control group was used in the research. The study was conducted on 36 participants who were divided into 3 groups of 12 pupils, one of which was experiment group and two of which were control groups. “Spence Children’s Anxiety Scale” was used in order to determine the anxiety level. The impact size has been determined as 56.3% for experiment group. The results of the study show that school-based cognitive behaviour program is effective.